Nowhere special [videorecording (DVD)] - Pasolini, Uberto; Norton, James, 1985-; Lamont, Daniel (Actor); O'Higgins, Eileen (Contemporary classics (Cohen Media Group), 2024)
John, a 35-year-old window cleaner, has dedicated his life to bringing up his 4-year-old son, Michael, after the child's mother left them soon after giving birth. When John is given only a few months left to live, he attempts to find a new, perfect family for Michael, determined to shield him from the terrible reality of the situation. As John struggles to find the right answer to his impossible task, he comes to accept the help of a young social worker, opening himself to solutions he would never have considered. And he finally comes to accept his anger at the injustice of his destiny, the need to share the truth with his son, and to follow the child's instincts on the biggest decision of their lives.